Exploring ICT pedagogic integration of economics teachers in two Johannesburg schools - Mlotshwa, Handson Fingi (My University, 2019)
This study was designed to investigate how teachers make meaning of the concept of ICT integration and to determine pedagogic value in their practice. This study assumed that teaching and learning are a form of dialogue as conceptualized by Laurillard (1999). The conceptual framework developed also drew on the interactive equivalency theorem (Miyazoe and Anderson, 2010) and the taxanomy of affordances (Conole and Dyke, 2004). Data was collected through both interviews and classroom observations. The interaction equivalency theorem was used to analyze the different interaction modes that happen in the classroom. The study found that learner to teacher interaction was the most common and dominant interaction facilitated by the technology. In learner to learner interaction, ICT use was limited to the projection of group activity. In learner to content interaction ICT was predominantly utilized as a source of content through videos, images and text in slides. The key finding of this research is that the use of ICTs can enhance classroom interaction in teaching FET economics.
Submitted in partial fulfillment of the requirements of the Master of Education by Coursework and Research Report, M.Ed., at the University of the Witwatersrand March 2019
Keywords: Educational technology--South Africa; Economics--Study and teaching; Information technology